Physical Condition Profile of Proton FC Futsal Players - Julinur Hafid; Muhamad Suma Wijaya; Rifki Rosad; Anisa Shopiani; Lilis Maesaroh; Mochamad Egi Margiyan (Jurnal Master Penjas & Olahraga, 2025)
This study aimed to determine the physical condition profile of Proton FC futsal players. The research employed a quantitative descriptive method with an observational descriptive design using survey techniques, tests, and measurements to describe the athletes’ physical components. The population consisted of 21 Proton FC futsal players, and total sampling was applied, meaning all players were included as research participants. The instruments used included flexibility (sit and reach), speed (20-meter sprint and agility pro), lower-body strength (hop and board jump), lower-body muscular endurance (hurdle jump), and cardiovascular endurance (Yo-Yo Intermittent Recovery Test Level 2). Data analysis was conducted using descriptive statistics to determine the mean values and physical condition categories of the players. The results indicated that overall physical condition was categorized from moderate to very good. Agility and lower-body explosive power were in good to very good categories, while speed and cardiovascular endurance were in the moderate category.